Socioeconomic and Demographic Causes of Crime Reporting in Indonesia - Rajagukguk, Wilson (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2023)
Studies on the nexus between socioeconomic and demographic factors and crime reporting are still limited in Indonesia. Therefore, this study aimed to investigate the socioeconomic and demographic causes of crime reporting in Indonesia using data from the results of the 2021 National Socioeconomic Survey. The data were analyzed using a binary logistic regression model. The unit of analysis was the population aged 15 years and older. The dependent variable was whether or not someone who experienced a crime reported it to the police. The independent variables were socioeconomic and demographic factors. The results of the study showed that a lower probability of reporting crime to the police was associated with being female, being younger, having higher educational attainment, living in urban areas, living in Java island, and working, implying the need to improve information, education, and communication on crime reporting among these groups.JEL Classification: A12, J19, K00, K39How to Cite:Rajagukguk, W. (2023). Socioeconomic and Demographic Causes of Crime Reporting in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 413-424. https://doi.org/10.15408/sjie.v12i2.33436.